2021
DOI: 10.1186/s12958-021-00754-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular microRNAs: key players to explore the outcomes of in vitro fertilization

Abstract: Background MicroRNAs (miRNAs) are small RNA molecules that modulate post-transcriptional gene regulation. They are often used as promising non-invasive biomarkers for the early diagnosis of cancer. However, their roles in assisted reproduction are still unknown. Methods This prospective study was designed to evaluate the expression profiles of seven extracellular miRNAs (miR-7-5p, miR-202-5p, miR-378-3p, miR-224, miR-320a, miR-212-3p, and miR-21-5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…Previous studies have shown that serum, follicular fluid and granulosa cells release large amounts of microvesicles containing both coding and noncoding RNAs, including miRNAs with multiple functional properties 16 19 . Thus, we hypothesized that PCOS-FF-exosomes might enhance apoptosis of granulosa cells by transferring specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that serum, follicular fluid and granulosa cells release large amounts of microvesicles containing both coding and noncoding RNAs, including miRNAs with multiple functional properties 16 19 . Thus, we hypothesized that PCOS-FF-exosomes might enhance apoptosis of granulosa cells by transferring specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…This role was confirmed by the study of Gay and colleagues, in which the knockout of the miR-202-5p gene in medaka ovaries reduced the expression of the Gdf and Foxl2b genes, resulting in either no oogenesis or the reduced production of oocytes that later fail to mature and fertilize [ 82 ]. The recently published prospective study by Khan and coworkers examined the expression profiles of several extracellular miRNAs in human follicular fluid with the aim of investigating the outcomes of the IVF/ICSI [ 115 ]. They examined a panel of several differentially expressed miRNAs (miR-7-5p, miR-202-5p, miR-378-3p, miR-224, miR-320a, miRNA-212-3p and miR-21-5p) that successfully discriminated between women with normoandrogenic PCOS and women with normal ovarian tests.…”
Section: Discussionmentioning
confidence: 99%
“…There is not yet sufficient and convincing evidence regarding the role of dysregulated miRNA in assisted reproductive technology. The results of Khan et al show the significantly differential expression of miR-320a in best-quality embryos compared with nonbest-quality embryos, with a sensitivity of 80% and a specificity of 71% (AUC = [0.753 (0.651; 0.855)], p = 0.001) [ 115 ]. Although there is growing evidence for the direct contribution of an altered miRNA profile and the potential for tailored IVF treatment strategies in the management of infertility, endometrial receptivity remains a limiting step for the overall success of IVF in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterized by high stability and disease-specific expression, the detection of extracellular miRNAs may provide novel and non-invasive biomarkers for embryo quality. Until now, several studies have reported that extracellular miRNAs may be associated with embryo development and implantation (15,16,28,29,(40)(41)(42)(43)(44)(45)(46)(47)(48). Rosenbluth et al (40) reported that decreased miR-372-3p and miR-373-3p in the ScM was associated with unsuccessful pregnancies.…”
Section: Discussionmentioning
confidence: 99%